USING DEBATING ACTIVITIES TO FOSTER STUDENTS’ COMMUNICATION AND CRITICAL THINKING SKILL - DENI ASRIDA (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2012)
This article discusses about the use of the debating activities in fostering students’ communication and critical thinking skills. The aims of debating are to enable the students to be active and creative in the classroom. Debating is also assumed as a valuable learning activity for teaching critical thinking and improving communication skills. Debating is an effective pedagogical way because of the level of responsibility for learning and active involvement required by all student debaters. Many teachers realize that the best strategy for motivating the students to communicate in English is by changing the situation in the class. By creating an interesting and motivating environment, the students are expected to be immersed in the activities given by the teachers. Moreover, an ideal teacher should provide opportunities for students to talk by using group work or pair work, and limiting teacher talk. Therefore, the teacher should keep encouraging the students to get involved during the process of learning in the class most of the time.